Effect of steam addition on the flow field and NOx emissions for Jet-A in an aircraft combustor - Xue, Rui; Hu, Chunbo; Nikolaidis, Theoklis; Pilidis, Pericles (Freund Publishing House / De Gruyter, 2015)
The steam injection technology for aircraft engines is gaining rising importance because of the strong limitations imposed by the legislation for NOx reduction in airports. In order to investigate the impact of steam addition on combustion and NOx emissions, an integrated performance-CFD-chemical reactor network (CRN) methodology was developed. The CFD results showed steam addition reduced the high temperature size and the radical pool moved downstream. Then different post-processing techniques are employed and CRN is generated to predict NOx emissions. This network consists of 14 chemical reactor elements and the results were in close agreement with the ICAO databank. The established CRN model was then used for steam addition study and the results showed under air/steam mixture atmosphere, high steam content could push the NOx formation region to the post-flame zone and a large amount of the NOx emission could be reduced when the steam mass fraction is quite high.
Keywords: chemical reactor network; steam dilution; aircraft engine; NOx emissions; CFD